Managing Functional Power: In Vision Driven Digital Media Creation - Rosenstand, Claus A. Foss; Laursen, Per Kyed (Academic Quarter | Akademisk kvarter, 2013)
How does one manage functional power relations between leading functions in vision driven digital media creation, and this from idea to master during the creation cycle? Functional power is informal, and it is understood as roles, e.g. project manager, that provide opportunities to contribute to the product quality. The area of interest is the vision driven digital media industry in general; however, the point of departure is the game industry due to its aesthetic complexity. The article's contribution to the area is a power graph, which shows the functional power of the leading functions according to a general digital media creation cycle. This is used to point out potential power conflicts and their consequences. It is concluded that there is normally more conflict potential in vision driven digital media creation than in digital media creation in general or in software development. The method is collaborative practice studies including action research and practice studies; combined with solid industrial experience.